2021
DOI: 10.3390/ijms22168568
|View full text |Cite
|
Sign up to set email alerts
|

Function and Mechanism of Jasmonic Acid in Plant Responses to Abiotic and Biotic Stresses

Abstract: As sessile organisms, plants must tolerate various environmental stresses. Plant hormones play vital roles in plant responses to biotic and abiotic stresses. Among these hormones, jasmonic acid (JA) and its precursors and derivatives (jasmonates, JAs) play important roles in the mediation of plant responses and defenses to biotic and abiotic stresses and have received extensive research attention. Although some reviews of JAs are available, this review focuses on JAs in the regulation of plant stress responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
129
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(134 citation statements)
references
References 200 publications
5
129
0
Order By: Relevance
“…It is fundamentally important to recognize how plants perceive stress signals and respond to various environmental stress factors [6]. Plant hormones are active members of the signal cascade involved in the generation of plant responses to stress conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is fundamentally important to recognize how plants perceive stress signals and respond to various environmental stress factors [6]. Plant hormones are active members of the signal cascade involved in the generation of plant responses to stress conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…An in-depth analysis of the biological process annotation of GO revealed that LOC_Os09g13610 was involved in the biological process of jasmonic acid (JA) mediated signalling pathway (GO:0009867). Previous studies had revealed that the hormone JA is a critical regulator of tolerance to abiotic stresses [47,48]. In addition, we found that two genes (LOC_Os04g32020 and LOC_Os09g14670) were involved in the tricarboxylic acid cycle process (GO:0006099), one gene (LOC_Os04g32070) was involved in the oxidation-reduction process (GO:0055114), and one gene (LOC_Os09g15670) was involved in the abiotic stress responses (GO:0009409, GO:0009414).…”
Section: Discussionmentioning
confidence: 79%
“…For example, under osmotic stress, the expression level of several ABA biosynthesis genes (such as ZEP, NCED) is upregulated [40]. In addition, JA and SA are involved in the defense response to biotic stress [41,42]. Under abiotic stress, the expression of LOX in the JA synthesis pathway is induced [42].…”
Section: Plant Hormone-associated Gene Expressionmentioning
confidence: 99%
“…In addition, JA and SA are involved in the defense response to biotic stress [41,42]. Under abiotic stress, the expression of LOX in the JA synthesis pathway is induced [42]. To limit the growth of pathogens and their access to water and nutrients in plants, the activation of SA-dependent signaling pathways could lead to the expression of PRP [43].…”
Section: Plant Hormone-associated Gene Expressionmentioning
confidence: 99%